TaWI12 may be involved in pistillody and leaf cracking in wheat - Yuhuan Guo; Yan Zhang; Yuhao Li; Yichao Wu; Mingli Liao; Zhengsong Peng; Zaijun Yang; Yonghong Zhou (BMC Plant Biology)
Abstract TaWI12 is a member of the wound-induced (WI) protein family, which has been implicated in plant stress responses and developmental processes. Wheat (Triticum aestivum L.) is a crucial staple crop upon which human sustenance relies. Consequently, investigating the developmental mechanisms of pistils and stamens in wheat is profoundly significant for enhancing wheat characteristics and boosting productivity. In this study, we cloned TaWI12, from common wheat and observed a significant resemblance among the three homoeologs of TaWI12. The open reading frames (ORFs) of TaWI12-4A, TaWI12-4B and TaWI12-4D were 408 bp, 417 bp and 417 bp, respectively, and encoded 135, 138 and 138 amino acids, respectively. The phylogenetic tree revealed a high degree of homology between the protein sequences of TaWI12 and the wound-induced proteins of Hordeum vulgare (KAI4994568) and Aegilops tauschii (XP_020196548). To clarify the characteristics and functions of TaWI12 homoeologs, we obtained transgenic positive plants of Arabidopsis thaliana and observed significant filament shortening and decrease. Simultaneously, we used the CRISPR/Cas9 system to generate mutant plants via the modification of three homoeologs of TaWI12 in wheat. We noticed two distinct phenotypic differences in the knockout mutant. First, we observed the different degrees of homologous conversion of stamens to pistils in the single mutant TaWI12-4D. Second, we observed leaf cracking in both the single mutant TaWI12-4A and the double mutants TaWI12-4A and TaWI12-4D. Our findings further revealed that TaWI12 plays an important role in flower development, which is important for revealing the molecular mechanisms of pistil and stamen development in wheat and has important application value for high-yield wheat breeding.